Evaluation of Security Technology for Proactive Safety Management in Public Schools in Edo North Senatorial District of Edo State - Agbonkpolor, M. U.; Otoibhi, O. J.; Uruneden, H. T. (NIU Journal of Social Sciences; Vol 6 No 2 (2020): KIU Journal of Social Sciences, Vol. 6 No. 2, June 2020, 2020)
This study was designed to evaluate security technology for proactive safety management in public schools in Edo North Senatorial District of Edo State. It shows that there is statistically significant effect of school population size on the security technology for proactive safety management in public schools. About 35% of the variation in the security technology is explained by school population size (R2 = 0.325, p<0.05). The remaining 65% unexplained variation is largely due to variation in order variables outside the regression model. The regression model is statistically significant in terms of goodness of fit (F = 461.917, p<0.05). It shows that when the school is over populated that a poor security management will not be able to control the pupils without some technology devices being put in place. Also, the study found out that there is significant relationship between the school environment and security technology for proactive safety management. The position of the public schools within the communities becomes a problem since most of them are sited outside the town and hence faced with more security challenges. More so, the issue of the ownership of public schools is another important factor. Keywords: Security, technology devices, public school, safety management.